2002
DOI: 10.1007/pl00012593
|View full text |Cite
|
Sign up to set email alerts
|

Riverine quality at the Anthropocene: Propositions for global space and time analysis, illustrated by the Seine River

Abstract: The control of riverine quality (water, particulates) by human-related pressures is now a major feature of the Anthropocene era. A set of general typologies and approaches to address the complex relationships between pressures, environmental impacts and some of the related social responses is proposed here on the basis of various examples, among others the Seine basin. Riverine quality management is described through a dozen major types illustrated by river fluxes and riverine quality trends (ӷ10 years). A suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 39 publications
0
75
0
3
Order By: Relevance
“…Although riverine fluxes of nutrients and pollutants are generally increasing, they can also decrease if the anthropogenic retention (e.g. in reservoirs) and the transformation processes exceed the additional sources of material (Meybeck 2002).…”
Section: Analysis Of the Present Situation Of River Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although riverine fluxes of nutrients and pollutants are generally increasing, they can also decrease if the anthropogenic retention (e.g. in reservoirs) and the transformation processes exceed the additional sources of material (Meybeck 2002).…”
Section: Analysis Of the Present Situation Of River Systemsmentioning
confidence: 99%
“…Basin size should also be considered in further river basin analyses because, for pollution point sources, the impact severity is very much linked to the dilution capacity, i.e. to basin size as is observed for the Seine River (Meybeck 2002). The historical development of river engineering (dams, channelization, canals, irrigation), of the evolution of aquatic biocenoses (including species introduction, acclimatization, extinction, invasion), of thermal changes, radionuclide contamination and water-borne diseases should also be addressed to complement this river chemistry analysis.…”
Section: Historical Development and Possible Future Of River Syndromementioning
confidence: 99%
“…Comparing key reports of regulatory agencies like the US Army Corps of Engineers (Anonymous 1983 versus Anonymous 2002) also shows this change in paradigm. In addition, it is being recognised that natural and anthropogenic impacts in the spatial parts of the basin (brook, stream, river, estuary) exhibit differences in time response varying between days and centuries (Meybeck 2002).…”
Section: Sediments As Part Of the Systemmentioning
confidence: 99%
“…State of America, South Korea, Nepal and central Asia [11]- [19]. These studies showed that the anthropogenic activities greatly deteriorate the water quality in major rivers, passing through communities with an absence or inadequate wastewater treatment facilities [14].…”
Section: Introductionmentioning
confidence: 98%